Expert Service-Oriented Architecture in C#: Using the Web Services Enhancements 2.0 - Hasan, Jeffrey (Apress, 2012)
WE SOFTWARE ARCHITECTS and developers live in a fascinating time. With the release of the .NET Framework in 2000, Web services technology has swept into our programming toolset and into our collective consciousness. Web services are the killer application for XML. Web services are the “new way” to call distributed objects remotely. Web services will take all of our integration headaches away, and allow formerly incompatible systems to communicate again. What Microsoft developer has not recently thought to themselves, “Should I be building my application with Web services?” What .NET developer has not recently thought to themselves, “I’mconfused”? Every tidal wave has a genesis, and a momentum, and a final destination where it typically crashes head-on into a stable landmass and causes havoc and confusion. Web services technology is a tidal wave./